PENELITIAN PEMANFAATAN ASBUTON BUTIR DI KOLAKA SULAWESI TENGGARA - Nyoman Suaryana (Jurnal Jalan-Jembatan, 2008)
Nationally, Indonesia needs the asphalt materials was approximately 1.2 million tons each year and only 0.6 million tons can be provided by PT. Pertamina and the rest should be imported from another country. Meanwhile asphalt deposits are decreasing and the prices rise up following prices of world crude oil. A promising alternative to solve that problem is to use asbuton (asphalt buton) as a substitution of petroleum asphalt. In recent years, technology of asbuton have been rapidly developed, including buton granular asphalt, asbuton pre-blending and asbuton extraction. The result of full scale experiment in Kolaka, South East Sulawesi indicates that the asbuton material has the capability to substitute petroleum asphalt as well as to improve the pavement performance. Key words : asbuton, pavement performace, full scale experimental.